Chloramphenicol's Semi-Synthetic Derivatization And In Vitro Investigation Of Its Broad Spectrum Antimicrobial Activity - Sharma, Ritika; Rao, B. Rupa Venkateswara; Rathore, Abhinav; Balsane, Amol Sambhaji; K V, Roshini; Kumar Sahu, Tapan; Badal, Shailendra; Rawat, Moni (Journal of Neonatal Surgery, 2025)
Chloramphenicol, a potent antibiotic with broad-spectrum activity, has been subject to semi-synthetic derivatization to enhance its therapeutic efficacy and overcome resistance mechanisms. This study aimed to synthesize novel semi-synthetic derivatives of chloramphenicol and evaluate their antimicrobial activity against a wide range of bacterial pathogens in vitro. The derivatives were synthesized using established chemical methods, with structural modifications focused on key functional groups known to influence the antibiotic activity of chloramphenicol. The antimicrobial activity of the derivatives was assessed using standard susceptibility testing methods, including agar diffusion and broth microdilution assays. The results revealed significant variations in the antimicrobial potency of the derivatives compared to chloramphenicol, with some derivatives exhibiting enhanced activity against certain bacterial strains. Furthermore, the derivatives demonstrated a broad spectrum of antimicrobial activity, including activity against both gram-positive and gram-negative bacteria. This study highlights the potential of semi-synthetic derivatization as a strategy to optimize the therapeutic profile of chloramphenicol and expand its utility in the treatment of infectious diseases.